Pearls & Oy-sters: Hemiballism and Orbitofrontal-like Syndrome in a Patient With Unilateral Tuberothalamic Stroke. (4th October 2022) - Grassl, Niklas; Ebert, Anne D.; Szabo, Kristina; Aghazadeh, Yashar; Platten, Michael; Alonso, Angelika
Abstract : Unilateral tuberothalamic stroke frequently causes behavioral changes and impairment of recent memory, especially in the left hemisphere, whereas motor signs are mostly minimal or even absent.